A new Oxyspirura (Nematoda, Thelaziidae) in three captive non-human primate species - Máca, Ondřej; González-Solís, David (Frontiers in Veterinary Science, 2025)
Members of Oxyspirura are mainly parasites in the eye of a wide variety of wild and domestic birds, as well as of some mammals. The latter group is represented by species found in non-human primates from zoological gardens. Recently, dead non-human primates of 12 species were examined to determine those with infections in the eyes, as well as their morphological and molecular identification. For that, 14 and six individual nematodes were used for the morphological and molecular analyses (18S rRNA, 28S rRNA, ITS, and cox1 genes), respectively. Three out of the 12 non-human primate species (Leontopithecus chrysomelas, Saguinus midas, and Saguinus oedipus) showed eye infection with nematodes, whose specific identification resulted in the erection of a new species, Oxyspirura (Oxyspirura) tamarina sp. nov. This species is characterized by having a divided buccal capsule, spicules unequal and dissimilar, gubernaculum present or absent, and variability in the number of precloacal papillae. All newly generated sequences were identical to each other. The new species differs morphologically from its congeners in the shape of the buccal capsule, length of spicules, and number and distribution of caudal papillae; molecularly, the genetic divergence was higher than 5% in all markers. Despite the morphological differences of the nematodes studied, the molecular analysis allowed us to recognize them as a sole species, thus becoming the third species of Oxyspirura reported in primates kept in captivity around the world.